2020
DOI: 10.1371/journal.pone.0234763
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of COVID-19 spreading profiles in South Korea, Italy and Iran by data-driven coding

Abstract: This work applies a data-driven coding method for prediction of the COVID-19 spreading profile in any given population that shows an initial phase of epidemic progression. Based on the historical data collected for COVID-19 spreading in 367 cities in China and the set of parameters of the augmented Susceptible-Exposed-Infected-Removed (SEIR) model obtained for each city, a set of profile codes representing a variety of transmission mechanisms and contact topologies is formed. By comparing the data of an early … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 12 publications
1
50
0
Order By: Relevance
“…General characteristics of reviewed studies: We found 13 articles and 10 reports and included eight published articles / preprint manuscripts [16][17][18][19][20][21][22][23] and three reports [13,24,25]. From the 13 found articles, three articles were kept for a next version of this review [8][9][10], one article was excluded because it was not an epidemic estimation study, and one article was excluded because of absent minimum necessary details on methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…General characteristics of reviewed studies: We found 13 articles and 10 reports and included eight published articles / preprint manuscripts [16][17][18][19][20][21][22][23] and three reports [13,24,25]. From the 13 found articles, three articles were kept for a next version of this review [8][9][10], one article was excluded because it was not an epidemic estimation study, and one article was excluded because of absent minimum necessary details on methods.…”
Section: Resultsmentioning
confidence: 99%
“…Appendix Figure 1 shows the PRISMA studies ow diagram. Four of the eight reviewed articles were published (Moradi et al, Tuite et al, Zareie et al, Zhuang et al) [18,20,21,23] and the other four were in preprint phase at the time that we reviewed them (Ahmadi et al, Ghaffarzadegan et al, Muniz-Rodriguez et al, Zhan et al) [16,17,19,22]. All articles were written in English, and all reports were written in Farsi.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the authorities have started to confront this epidemic by shutting down the schools and universities, refusing non-local travelers in some provinces, reducing working hours for some days, implementing forms of remote work by many companies for the employees, requesting the individuals to stay at home in self-quarantine, etc., still there is a quick increase in the number of infected cases [5]. According to the literature review, there are limited published papers on Iran's status in the outbreak period of the COVID-19 [5,[14][15][16][17][18]. Therefore, given the rapid outbreak of the COVID-19 in Iran, this study was conducted in order to identify the spreading trend of this disease in Iran and all its provinces from February 19 to March 22, 2020, using the recorded data from the MHME and also to find similar provinces according to the disease spread using K-means cluster analysis (KMCA).…”
Section: Introductionmentioning
confidence: 99%